Samayadarśī sāhityasandarbha kośa - Sonī, Ramaṇa (Gujarāta Sāhitya Akādamī, 2012)
Chronological reference work of Gujarati authors and Gujarati literature
Keywords: Wörterbuch; Authors; Gujarati; Gujarati literature; Écrivains gujarātī - 20e siècle - Biographies; Bio-bibliography; Biographies